Convergence analysis of a coefficient inverse problem for the semi-discrete damped wave equation. Issue 4 (4th March 2022) - Zhang, Wensheng; Zhao, Zhongliu
ABSTRACT: In this paper, we study the convergence of a coefficient inverse problem for the two dimensional semi-discrete damped wave equation. Based on the new discrete Carleman estimates for the semi-discrete wave operator, the uniform stability estimate is proved. Then we prove the convergence of the semi-discrete scheme with respect to the discretization grid step h >0.